Characteristics of the molecular diversity of the outer membrane protein A gene of Haemophilus parasuis - Tang, Cheng (Canadian Veterinary Medical Association, 2010)
The molecular diversity of the gene encoding the outer membrane protein A (OmpA) of Haemophilus parasuis has been unclear. In this study, the structural characteristics, sequence types, and genetic diversity of ompA were investigated in 15 H. parasuis reference strains of different serovars and 20 field isolates. Three nucleotide lengths of the complete open reading frame (ORF) of ompA were found: 1098 base pairs (bp), 1104 bp, and 1110 bp. The OmpA contained 4 hypervariable domains, mainly encoding the 4 putative surface-exposed loops, which makes it a potential molecular marker for genotyping. Western blot analysis showed that the recombinant OmpAs of serovars 4 and 5 could cross-react with antiserum to all 15 serovars. Hence, although ompA of H. parasuis exhibited high variation among serovars, this variation did not seem to affect the strong antigenic characteristics of OmpA.